Impact of refugia and integrated pest management on the performance of transgenic (Bacillus thuringiensis) cotton (Gossypium hirsutum) - BAMBAWALE, O M; TANWAR, R K; SHARMA, O P; BHOSLE, B B; LAVEKAR, R C; PATIL, S B; DHANDAPANI, A; TRIVEDI, T P; JEYAKUMAR, P; GARG, D K; JAFRI, A A; MEENA, B L (The Indian Journal of Agricultural Sciences, 2010)
Farmers' participatory field trials were conducted with transgenic (Bacillus thuringiensis) and conventional cotton (Gossypium hirsurum L.) hybrids in integrated pest management and non-integrated pest management modes using different combinations of refugia for two cropping seasons (2003-05) in Nanded district of Maharashtra in central India and one cropping season (2004-05) in Dharwad district of Karnataka of southern India. At Nanded, the experiments were conducted with Br 'MECH 184' and local popular conventional hybrid 'Bunny' and at Dharwad with 'RCH 2' Br and 'RCH 2' conventional popular cotton hybrid. Results on sucking pests indicated no consistent trend with regard to locations and cropping seasons in Br and conventional cottons. The mean incidence of American boliworm (Helicoverpa armigera Hubner), pink bollworm (Pectinophora gossypiella Saunders) and spotted bollworm (Earias insulana Boisd.) larval population and percentage of damaged squares, boils and shed fruiting bodies at both the locations remained significantly high in conventional cotton treatments compared with all the Br cotton treatments. The population of ladybird beetle and Chrysoperla zastrowi arabica Henry et al. was not adversely affected in all Br treatments compared with the conventional cotton treatments. The yield data indicated higher seed cotton yield in all the Br treatments compared to conventional cotton at both the locations. Integrated pest management was necessary for getting the best out of Br cotton and 20% refugia reduced the seed cotton yield without giving substantial benefit in terms of bollworm control or conserving higher natural enemy population.